Exploring how translanguaging and multimodal learning improve EFL students - Hidayati, Dini; Dharmawan, Yanuarius Yanu; Prasatyo, Bayu Andika; Luciana, Luciana (Journal on English as a Foreign Language, 2024)
Many studies have shown that translanguaging promotes inclusive and dynamic learning environments. However, little is known about multimodal techniques to improve student engagement and satisfaction. The present study aims to examine the impact of these combined strategies on student understanding, motivation, and identity construction in language acquisition. The study involved twenty students in the second semester of the English Language Education Department at a university in Bekasi, West Java, Indonesia. The data were garnered through a quantitative method using a questionnaire and a qualitative method using in-depth interviews. Out of the total number of participants, five students were selected for in-depth interviews to explore rich data on students' emotional, motivational, cognitive, and expressive responses to translanguaging. The data obtained from the questionnaire were analyzed statistically while the data obtained from the interviews were analyzed using thematic analysis. The results suggest that adding translanguaging and multimodal strategies to the learning environment promotes a more engaging and inclusive atmosphere, thereby enhancing student satisfaction and language proficiency. Conversely, complications were identified for students with diminished proficiency requiring further assistance. The research emphasizes the potential of translanguaging to enhance linguistic competence, student confidence, and motivation, indicating that it is a valuable pedagogical tool in EFL classrooms.